English Education students’ perceptions regarding the workshop of using artificial intelligence for developing listening question based on local wisdom - Khanif, M. (FKIP UNILA, 2023)
This research aims to explore the students’ perceptions in the English Language Education Study Program at UIN Raden Mas Said Surakarta regarding the workshop on the use of artificial intelligence (AI) in developing listening questions based on local wisdom. The method used is descriptive qualitative involving students as research subjects. Data was collected through the use of questionnaires distributed to students and analysis was carried out using a qualitative approach to understand their views, thoughts and perceptions regarding the use of AI in the context of learning English, especially listening skills. The results of this research provide in-depth insight into how English Language Education students assess the relevance, benefits and obstacles in using AI to develop listening questions that integrate local wisdom. The implications of these findings can be used as a basis for developing a more adaptive and innovative curriculum in the context of English language teaching that accommodates aspects of local wisdom.